Hydrogen isotopic ratios of long-chain diols reflect salinity. (November 2019) - Lattaud, Julie; Erdem, Zeynep; Weiss, Gabriella M.; Rush, Darci; Balzano, Sergio; Chivall, David; van der Meer, Marcel T.J.; Hopmans, Ellen C.; Sinninghe Damsté, Jaap S.; Schouten, Stefan
Highlights: Refined separation method allows the δ 2 H measurement of long-chain diols. δ 2 H composition of long-chain diols of Nannochloropsis matches the growth medium. Hydrogen isotopic ratios of C32 1, 15-diol reflects its origin in fresh river water. Hydrogen isotopic ratios of C30 1, 15-diol reflects sea water isotopic composition. Abstract: Long-chain diols (LCDs) are ubiquitous lipids produced by freshwater and marine algae. A combination of semi-preparative high performance liquid chromatography and gas chromatography isotope ratio monitoring mass spectrometry, allowed the measurement of δ 2 H of individual LCDs from cultures, which indicated a correlation with the hydrogen isotope composition of the growth water and a species-specific effect. Results from environmental samples along a salinity gradient indicated the potential of δ 2 H ratios of LCDs to trace the hydrogen isotopic composition of water and sea surface salinity.